Structural studies on encapsulation of tetrahedral and octahedral anions by a protonated octaaminocryptand cage - Ravikumar, I.; Lakshminarayanan, P. S.; Suresh, E.; Ghosh, Pradyut (Beilstein Journal of Organic Chemistry, 2009)
Structural aspects of the binding of inorganic anions such as perchlorate, hydrogen sulfate, and hexafluorosilicate with the proton cage of octaaminocryptand L1, N(CH2CH2NHCH2-p-xylyl-CH2NHCH2CH2)3N), are examined thoroughly. Crystallographic results for a hexaprotonated perchlorate complex of L1, [(H6L1)6+(ClO4−)]5(ClO4−)·11H2O·CH3CN (1), an octaprotonated hydrogen sulfate complex of L1, [(H8L1)8+(HSO4−)]7(HSO4−)·3H2O·CH3OH (2) and an octaprotonated fluorosilicate complex of L1, [(H8L1)8+(HSiF6−)]3(SiF62−)·(HSiF6−)·15H2O (3), show encapsulation of one perchlorate, hydrogen sulfate and hexafluorosilicate, respectively inside the cage of L1 in their protonated states. Further, detailed structural analysis on complex 1 reveals that the hexaprotonated L1 encapsulates a perchlorate via two N–H···O and five O–H···O hydrogen bonds from protonated secondary nitrogen atoms of L1 and lattice water molecules, respectively. Encapsulated hydrogen sulfate in complex 2 is “glued” inside the octaprotonated cage of L1 via four N–H···O and six C–H···O hydrogen bonds whereas encapsulated HSiF6− in complex 3 has short contacts via six N–H···F and three C–H···F hydrogen bonds with [H8L1]8+. In the cases of complexes 2 and 3, the cryptand L1 in octaprotonated state shows monotopic encapsulation of the guest and the final conformation of these receptors is spherical in nature compared to the elongated shape of hexaprotonated state of L1 in complex 1.
Keywords: anion receptor; cryptand; molecular recognition; proton cage

Supramolecular Chemistry of Anions - Bianchi, A.; Bowman-James, K.; García-España, E. (Wiley-VCH, 1997)

35 Years of Synthetic Anion Receptor Chemistry 1968–2003 - Gale, P. A. (Coord. Chem. Rev., 2003)

The Encyclopedia of Supramolecular Chemistry - Atwood, J. L.; Steed, J. W. (Dekker, 2004)

Anion Coordination Chemistry II - Gale, P. A. (Coord. Chem. Rev., 2006)

(untitled) - Robinson, B. H.; Williams, G. R. (Biochem. Biophys. Acta, 1970)

Topics in Current Chemistry - Kimura, E. (Macrocyclic polyamines as biological cation and anion complexones – An application to calculi dissolution, 1985)

(untitled) - He, J. H.; Quicocho, F. A. (Science, 1991)

(untitled) - Barth, M. C.; Church, A. T. (J. Geophys. Res., 1999)

(untitled) - Hossain, Md A.; Llinares, J. M.; Mason, S.; Morehouse, P.; Powell, D.; Bowman-James, K. (Angew. Chem., Int. Ed., 2002)

(untitled) - Hossain, Md A.; Morehouse, P.; Powell, D.; Bowman-James, K. (Inorg. Chem., 2005)

(untitled) - Lakshminarayanan, P. S.; Kumar, D. K.; Ghosh, P. (Inorg. Chem., 2005)

(untitled) - Lakshminarayanan, P. S.; Suresh, E.; Ghosh, P. (Angew. Chem., Int. Ed., 2006)

(untitled) - Lakshminarayanan, P. S.; Ravikumar, I.; Suresh, E.; Ghosh, P. (Cryst. Growth Des., 2008)

(untitled) - Hossain, Md A.; Morehouse, P.; Powell, D.; Bowman-James, K. (Inorg. Chem., 2005)

(untitled) - Alcock, N. W.; Bowman-James, K.; Miler, C.; Berenguer, J. M. L. (Private Communication, 2005)

(untitled) - Mason, S.; Llinares, J. M.; Morton, M.; Clifford, T.; Bowman-James, K. (J. Am. Chem. Soc., 2000)

(untitled) - Menif, R.; Reibenspies, J.; Martell, A. E. (Inorg. Chem., 1991)

(untitled) - Mason, S.; Clifford, T.; Seib, L.; Kuczera, K.; Bowman-James, K. (J. Am. Chem. Soc., 1998)

(untitled) - Hynes, M. J.; Mauber, B.; McKee, V.; Town, R. M.; Nelson, J. (J. Chem. Soc., Dalton Trans., 2000)

(untitled) - Maubert, B. M.; Nelson, J.; McKee, V.; Town, R. M.; Pál, I. (J. Chem. Soc., Dalton Trans., 2001)

(untitled) - Nelson, J.; Nieuwenhuyzen, M.; Pál, I.; Town, R. M. (Chem. Commun., 2002)

(untitled) - Farrell, D.; Gloe, K.; Gloe, K.; Goretzki, G.; McKee, V.; Nelson, J.; Nieuwenhuyzen, M.; Pál, I.; Stephan, H.; Town, R. M.; Wichmann, K. (Dalton Trans., 2003)

(untitled) - Morgan, G.; McKee, V.; Nelson, J. (J. Chem. Soc., Chem. Commun., 1995)

(untitled) - Kang, S. O.; Hossain, M. A.; Powell, D.; Bowman-James, K. (Chem. Commun., 2005)

(untitled) - McKee, V.; Morgan, G. G. (Acta Crystallogr., 2003)

(untitled) - Yang, L.-Z.; Jiang, L.; Feng, X.-L.; Lu, T.-B. (CrystEngComm, 2008)

(untitled) - Reyheller, C.; Kubik, S. (Org. Lett., 2007)

(untitled) - Hossain, Md A.; Llinares, J. M.; Powell, D.; Bowman-James, K. (Inorg. Chem., 2001)

(untitled) - Katayev, E. A.; Boev, N. V.; Khrustalev, V. N.; Ustynyuk, Y. A.; Tananaey, I. G.; Sessler, J. L. (J. Org. Chem., 2007)

(untitled) - Sessler, J. L.; Katayev, E.; Pantso, G. D.; Ustynyuk, Y. A. (Chem. Commun., 2004)

(untitled) - Sessler, J. L.; Katayev, E.; Pantos, G. D.; Scherbakov, P.; Reshetova, M. D.; Khrustalev, V. N.; Lynch, V. M.; Ustynyuk, Y. A. (J. Am. Chem. Soc., 2005)

(untitled) - Clifford, T.; Dnaby, A.; Llinares, J. M.; Mason, S.; Alcock, N. W.; Powell, D.; Aguilar, J. A.; Garcìa-España, E.; Bowman-James, K. (Inorg. Chem., 2001)

(untitled) - McKee, V.; Nelson, J.; Town, R. M. (Chem. Soc. Rev., 2003)

(untitled) - IIioudis, C. A.; Tocher, D. A.; Steed, J. W. (J. Am. Chem. Soc., 2004)

(untitled) - Abouderbala, L. O.; Belcher, W. J.; Boutelle, M. G.; Cragg, P. J.; Steed, J. W.; Turner, D. R.; Wallace, K. J. (Proc. Natl. Acad. Sci. U. S. A., 2002)

An Introduction to Hydrogen Bonding - Jeffery, G. A. (Oxford Univ. Press, 1997)

(untitled) - Braga, D.; Grepioni, F.; Desiraju, G. R. (Chem. Rev., 1998)

(untitled) - Arya, P.; Channa, A.; Cragg, P. J.; Prince, P. D.; Steed, J. W. (New J. Chem., 2002)